The comparison of three different molecular imaging methods in localization and grading of insulinoma - Chang, Lina; Bi, Xinyu; Li, Shuo; Tong, Qi; Gu, Yian; He, Zonghao; Li, Yansheng; Chen, Qiusong; Cui, Jingqiu; Yu, Haonan; He, Qing; Liu, Ming (Frontiers in Endocrinology, 2023)
Aims: This cross-sectional study compared the value of molecular imaging (Exendin-4 positron emission tomography/computed tomography [PET/CT], 68Ga-DOTATATE PET/CT, 18F- fluorodeoxyglucose [FDG] PET/CT) in insulinoma localization by stratified tumor size and grading, and explored the correlation of the related SUVmax with insulinoma grading, Ki-67, maximum tumor diameter, and glucose metabolism. Methods: In 28 insulinoma patients, the sensitivity of three types of PET/CT for localizing insulinoma was calculated according to tumor size and grade. We compared the SUVmax for different insulinoma grades and analyzed the correlation of SUVmax with Ki-67, maximum tumor diameter, and glucose metabolism indicators. Results: The study included 12 grade (G) 1 and 16 G2 cases, with maximum tumor diameters ranging from 9 to 40 mm. Without differentiation by size and grade, the sensitivity of Exendin-4 PET/CT to localize insulinoma was 100%, which significantly exceeded that of 68Ga-DOTATATE PET/CT and 18F-FDG PET/CT (75% and 57%, respectively). In tumors with a maximum diameter ≤ 20 mm and ≤ 15 mm, the sensitivity of Exendin-4 (both 100%) significantly exceeded that of 68Ga-DOTATATE PET/CT (74% and 64%, respectively) and 18F-FDG PET/CT (54% and 50%, respectively). In G1 tumors, the sensitivity of Exendin-4 PET/CT was significantly higher than that of 18F-FDG PET/CT, but not that of 68Ga-DOTATATE PET/CT, while in G2 tumors, the sensitivity of Exendin-4 PET/CT was significantly higher than that of both other types. However, all three PET/CT types missed a metastatic lymph node in one patient. The 18F-FDG PET/CT SUVmax was significantly lower than that of the other PET/CT types and that of 68Ga-DOTATATE PET/CT was significantly lower in G2 than in G1. 68Ga-DOTATATE PET/CT SUVmax correlated negatively with Ki-67. A receiver operating characteristic (ROC) curve suggested that 68Ga-DOTATATE PET/CT SUVmax > 19.9 could predict G1 tumors. Conclusions: Exendin-4 PET/CT was superior to 68Ga-DOTATATE PET/CT and 18F-FDG PET/CT for insulinoma localization, particularly small and G2 tumors, but its diagnostic value in small metastatic lymph nodes requires further exploration. 68Ga-DOTATATE PET/CT SUVmax could be used as an adjunct to pathology, and a value > 19.9 could predict G1 tumors. No PET/CT SUVmax could predict tumor maximum diameter and glucose metabolism.